2020
DOI: 10.1108/caer-09-2019-0162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of changing income distribution on fluid milk consumption in urban China

Abstract: PurposeChina has experienced a fast economic growth and shown a significant rise in income inequality in the past decades. During the same period, fluid milk consumption in urban areas has rapidly expanded. The objective of this paper is to analyze and simulate the influence of income distribution changes on fluid milk consumption of households in urban China.Design/methodology/approachThis study applies an inverse hyperbolic sine (IHS) double-hurdle model to modeling at-home fluid milk consumption of househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The predicted results for animal source foods show that eggs, as the most widely consumed source of daily protein intake by Chinese residents, will show a rigid growth trend in consumption demand. Additionally, beef, mutton, dairy, and seafood are high-quality products and essential sources of high-quality protein in the diet [ 2 ]. The growth in demand for these four food items illustrates the growing diversified dietary needs of the Chinese population, which indicates that the Chinese dietary transition will continue to shift from the traditional fiber-dominated food system to a Western-style meat-dominated diet [ 1 , 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The predicted results for animal source foods show that eggs, as the most widely consumed source of daily protein intake by Chinese residents, will show a rigid growth trend in consumption demand. Additionally, beef, mutton, dairy, and seafood are high-quality products and essential sources of high-quality protein in the diet [ 2 ]. The growth in demand for these four food items illustrates the growing diversified dietary needs of the Chinese population, which indicates that the Chinese dietary transition will continue to shift from the traditional fiber-dominated food system to a Western-style meat-dominated diet [ 1 , 4 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of this extensive dataset is that the chosen households in the survey recorded their food consumption and expenditure characteristics using a diary for over a year, which accurately captured the consumption behavior of Chinese households. The data are widely used in Chinese food consumption and related empirical studies [ 2 , 43 , 44 , 45 ]. Therefore, the dataset used in this study is of high quality and can more realistically reflect the dietary features across different income strata in China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimation of food demand elasticity is an important aspect of food consumption research [ 25 ]. Researchers have constructed various models to estimate the price elasticity of food demand and the income (or expenditure) elasticity of demand for food among Chinese residents based on utility maximization and budget constraints [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. It has been demonstrated that most income elasticity with respect to food demand in China is positive, as reviewed by Chen et al [ 33 ].…”
Section: Introductionmentioning
confidence: 99%